Implementasi Diagram UML (Unified Modelling Language) dalam Perancangan Aplikasi Data Pasien Rawat Inap pada Puskesmas Lubuk Buaya - Putra, Hendra Nusa (Sinkron : jurnal dan penelitian teknik informatika, 2018)
Health services to the community is the most important part to increase awareness, willingness and ability to live healthy for every person to realize the optimal health status of society. Patient or community satisfaction of the services provided by the puskemas is strongly influenced by the speed and determination of the officers in handling the patient, starting from the patient registering until the patient is examined by medical personnel to get the medication for the illness he complains about.Data collection of inpatients at Puskesmas Lubuk Buaya Padang is still using conventional way that records manual patient data in a book and in handling patient sometimes patient often forgot or lost her visit card when she return treatment then officer will directly return make visit card for missing. This method is certainly not maximal or less optimal so that many obstacles faced by the officers and patients who come treatment and also resulted in redundancy of data and reports that must be issued often experience delays. Stages of research that has been done by analyzing the system is running to produce a fast, accurate and easy information.Utilization of information system at puskesmas begins with software modeling (UML) which is a very reliable tool in developing object oriented system, while UML diagram used in this research is use case diagram, class diagram, activity diagram, sequence diagram, state diagrams and collaboration diagrams. so that obtained a systematic design for the design of applications using PHP and MySQL programming language.The design of patient data information system application that has been done for processing transaction data which was originally done manually into computerization can simplify the data processing so that it can be done quickly and accurately, and the information generated in the form of more complete report.